Optimizing the Locations and Sizes of Solar Assisted Electric Vehicle Charging Stations in an Urban Area - Dong Ji; Mingsong Lv; Jiayu Yang; Wang Yi (IEEE Access)
With the wide-spread adoption of electric vehicles (EVs), introducing solar energy in building EV charging stations is promising as it can reduce carbon emissions and improve air quality. The main challenges are how to decide where to build solar assisted charging stations in a city and how to size the charging stations, as the decision is affected by a broad range of factors, such as construction cost, solar energy fluctuation, and user requirements. This paper proposed an approach to efficiently decide the locations and sizes of solar energy assisted charging stations for an urban area. Experiments are conducted on real EV history data from 297 users of an EV leasing company. The results show that the proposed method can produce high quality decisions within reasonable computation time. The work of this paper will provide important information for decision makers to integrate solar energy into the EV charging infrastructure.